Full Day School: School Excellence Model Implementation Process For A Good Education - Yusuf, - (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
Full day school is a schooling program with the strategy of shortening the time outside schoolwith strategies learners get an extra hour to education, which designed to the process ofeducation and learning in primary schools and junior high schools.The idea of full day school is very feasible to minimize the negative influence of the homeenvironment and the community outside the school. Children in its activities became morefocused when in a school environment that is designed for the provision of good education.Full day school program already widely implemented in countries such as China, Japan andeven the United States. Results have demonstrated a positive thing for the development ofchildrens character. In Indonesia, the full day school program has been implemented in anumber of private schools, in the last year.Full day school program is applied in the model of integrated education is good, if theapplication is done thoroughly. Full day school program be tested in some urban public schoolsthat have the completeness of adequate infrastructure, as well as private schools who areinterested. This program can help difficulties urban parents who generally work all day. With afull day school children after school can follow the activities of deepening subjects and extracurricular activities to return along with the parents when they returned to work, did not gohome without supervision from the family and school.It required a thorough investigation before the policy is applied. As the emergence of the extracost for lunch Child, and The financing activities carried learners after completion of thelearning process. Studies on the policy to determine the target of education, programs to beexecuted, the readiness of staff, facilities infrastructures, financing and more.Keywords: Full day school, integrated Education, Islamic Education within the framework of integratededucation